COMPARATIVE ANTI-DIABETIC EFFECTS OF ETHANOL EXTRACTS FROM LEAVES, SEEDS and PODS OF Moringa oleifera ON ALLOXAN INDUCED DIABETIC RATS - Adebayo, Kingsley O.; Owolabi, M. A.; Khan, M. E. (FUDMA JOURNAL OF SCIENCES, 2024)
The anti-diabetic activity of 30 % ethanol extract of seeds, pods, leaves of Moringa oleifera was evaluated on induced diabetic rats for 4 weeks. After the treatment with extracts, the animals were sacrificed by cervical dislocation for the histopathological examination of their pancreas.  Saponin and volatile oil were high in pod extract whereas high alkaloids, flavonoids, flavanols and anthraquinones were detected in all extracts. For bioassay, the animals were grouped into A, B, C, D, E, and F corresponding to treatment with 200 mg leave extract per kg body weight, 4 mL seed extract per kg body weight, 300 mg pod extract per kg body weight, 1.0 mL normal saline (diabetic control), 10 mg of metformin per kg body weight, 1.0 mL normal saline (Normal control) respectively. At the end of the treatment, it was found that 300 mg pod extract per kg body weight reduced the blood glucose level from 492.80 mg/dL to 128.30 mg/dL while 200 mg of leave extract per kg body weight reduced blood glucose level from 423.00 to 212.30 mg/dL. It was found that the antihyperglycaemic activity of 300 mg/kg pod extract is comparable to the standard drug. Also the observed activity was more for 300 mg/kg pod extract than 200 mg/kg leave extracts. Moreover at p > 0.005, there is a statistically significant difference between the blood glucose of the animals before and after they were treated for 28 days with both pod and leave extracts. Both leaves and pod extracts indicated antidiabetic activity,...
Keywords: Antidiabetic; Histopathological; Antihyperglycaemic; Bioassay